2017
DOI: 10.1073/pnas.1702613114
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen exploitation of an abscisic acid- and jasmonate-inducible MAPK phosphatase and its interception by Arabidopsis immunity

Abstract: Phytopathogens promote virulence by, for example, exploiting signaling pathways mediated by phytohormones such as abscisic acid (ABA) and jasmonate (JA). Some plants can counteract pathogen virulence by invoking a potent form of immunity called effector-triggered immunity (ETI). Here, we report that ABA and JA mediate inactivation of the immune-associated MAP kinases (MAPKs), MPK3 and MPK6, in Arabidopsis thaliana. ABA induced expression of genes encoding the protein phosphatases 2C (PP2Cs), HAI1, HAI2, and HA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
91
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 48 publications
5
91
0
Order By: Relevance
“…The three HAI PP2Cs are not regulated by Enhancer of ABA co-Receptor 1 (EAR1), which promotes the activity of the six other Clade A PP2Cs and thereby affects ABA sensitivity (18). Also, Mine et al (19) found that the HAI PP2Cs, but not the Clade A PP2C ABI2, could interact with MPK3 and MPK6. They also demonstrated that HAI1 could directly dephosphorylate these MPKs.…”
Section: Introductionmentioning
confidence: 99%
“…The three HAI PP2Cs are not regulated by Enhancer of ABA co-Receptor 1 (EAR1), which promotes the activity of the six other Clade A PP2Cs and thereby affects ABA sensitivity (18). Also, Mine et al (19) found that the HAI PP2Cs, but not the Clade A PP2C ABI2, could interact with MPK3 and MPK6. They also demonstrated that HAI1 could directly dephosphorylate these MPKs.…”
Section: Introductionmentioning
confidence: 99%
“…However, MPK6 is required for stomatal closure in response to the bacterial elicitor flagellin (Montillet et al, 2013;Su et al, 2017) and it is required, in redundance with MPK3, for stomatal immunity involving altered organic acid metabolism (Su et al, 2017). In line with the results on ABA response in mpk6 mutants, it was recently shown that ABA inactivated MPK6 (Mine et al, 2017). MPK6 is activated upon bacterial infection, during both pattern-triggered and effector-triggered immunity.…”
Section: Regulation Of Almt4 By Phosphorylationmentioning
(Expert classified)
“…Some pathogens, such as Pseudomonas syringae pv tomato (Pto) DC3000, counteract immunity by activating, among others, ABA signaling, and ABA has been known to negatively impact immunity against Pto DC3000 (de Torres Zabala et al, 2009). Mine et al (2017) showed that ABA induced the expression of HAI phosphatases of the PP2C (protein phosphatase 2C)-type, which in turn inactivate MPK6 through dephosphorylation. Thus, one could speculate that active MPK6 shuts down ALMT4 in the ground state but that this kinase is inactivated in response to ABA, thus ceasing ALMT4 phosphorylation, causing Mal 22 efflux.…”
Section: Regulation Of Almt4 By Phosphorylationmentioning
confidence: 99%
“…Thus, our data identify PP2C phosphatase ABI1, which directly catalyzes a de-phosphorylation of calcium-regulated kinase CPK5 protein leading to enzyme activation and promotion of immune signaling. Interestingly, expression of PP2C phosphatase genes HAI1, HAI2, and HAI3 is induced in response to ABA, and respective phosphatase proteins can interact with, dephosphorylate and inactivate MAP kinases MPK3 and MPK6, which thereby leads to immune suppression (51). Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Trade-offs between biotic and abiotic stress responses allow a plant to prioritize the abiotic over the biotic stress responses (49). Mechanisms for prioritization against immune response may target rather early stages at the level of perception, for example through a control of the secretion and accessibility of PRR receptors in the PM (50), or at the level of signaling, for example through ABA-induced transcriptional activation of phosphatase genes, whose gene products catalyze an inactivation of immune-associated MAP kinases (51). Stress prioritization may also involve rather late stages, for example employing the phytohormone-mediated crosstalk, where ABA signaling suppresses SA synthesis and signaling and in such prohibiting SAdependent immunity (52,53).…”
mentioning
confidence: 99%